The THE EFFECT OF HEAD TILT-CHIN LIFT MANEUVER WITH RAMPED POSITION ON AIRWAY IN POST GENERAL ANESTHESIA PATIENTS WITH ENDOTRACHEAL TUBE AT RSUD WATES - Puti Nadja Maharani Nadjaaa; Ratih Kusuma Dewi; Joko Murdiyanto (Journal of Indonesian Anesthesiology Nursing, 2026)
ABSTRACT Background: Patients recovering from general anesthesia with an endotracheal tube are at risk of airway patency impairment due to decreased pharyngeal muscle tone, residual anesthetic effects, and incomplete recovery of airway protective reflexes. Simple interventions such as the head tilt-chin lift maneuver with a ramped position can help maintain airway patency Methods: This quantitative quasi-experimental study used a two-group pretest-posttest design with 48 respondents divided into intervention and control groups. Data were collected via observation sheets and analyzed using the Wilcoxon and Mann-Whitney U tests. Results: The result of Wilcoxon Signed Ranked Test in the intervention group showed p = 0.000 (p < 0.05), indicating a significant effect on airway patency. The control group showed p = 0.083 (p > 0.05), indicating no significant effect. The Mann-Whitney U Test showed p = 0.000 (p < 0.05), indicating a significant difference between the two groups. Conclusion: The head tilt-chin lift maneuver with a ramped position is effective in improving airway patency in post-general anesthesia patients with an endotracheal tube at RSUD Wates.